Pain without presence: a narrative review of the pathophysiological landscape of phantom limb pain - Wu, Hong; Saini, Chandan; Medina, Roi; Hsieh, Sharon L.; Meshkati, Aria; Sung, Kerry (Frontiers in Pain Research, 2025)
Phantom limb pain (PLP) is defined as the perception of pain in a limb that has been amputated. In the United States, approximately 30,000–40,000 amputations are performed annually with an estimated 2.3 million people living with amputations. The prevalence of PLP among amputees is approximately 64%. Over the years, various theories regarding the etiology of PLP have been proposed, with some gaining more prominence than others. Yet, there is a lack of consensus on PLP mechanisms as the current literature exploring the pathophysiology of PLP is multifactorial, involving complex interactions between the central and peripheral nervous systems, psychosocial factors, and genetic influences. This review seeks to enhance the understanding of PLP by exploring its multifaceted pathophysiology, including genetic predispositions. We highlight historical aspects of pain theories and PLP, examining how these theories have expanded to include psychosocial dimensions associated with chronic pain in amputees. Additionally, we present significant findings from both human and animal studies focused on neuroaxial systems and recent advances in molecular research to further elucidate the complex and multifactorial nature of PLP. Ultimately, we hope that the integration of current theoretical frameworks and findings will lay a more robust foundation for future research on PLP.